Transcatheter patent ductus arteriosus closure in very low birth weight preterm infants: early results and midterm follow-up - Liu, Junhui; Gao, Wei; Liu, Zigang; Zhao, Kun; Luo, Gang; Gao, Shuai; Sun, Yi; Pan, Silin (Frontiers in Pediatrics, 2025)
BackgroundAlthough transcatheter patent ductus arteriosus (PDA) closure is becoming increasingly common in very low birth weight (VLBW) preterm infants, several key issues remain controversial. These include identifying suitable patient characteristics, determining the optimal timing for PDA closure, preventing potential complications, and accurately assessing mid- and long-term outcomes. This study aims to summarize our preliminary experience in selecting appropriate patients and timing for PDA closure, and to report the early and mid-term outcomes of transcatheter PDA closure in VLBW preterm infants.MethodsThis was a single-center retrospective study. Eligible participants included preterm infants with gestational age <37 weeks and birth weight <1,500 g who underwent transcatheter PDA closure between January 2024 and January 2025 at Qingdao Women and Children's Hospital. Data on patient characteristics, procedural age, PDA closure, survival, and intraoperative or postoperative complications were collected. Outcomes were assessed immediately after the procedure, at discharge, and 6 months post-discharge.ResultsProcedures were performed in 8 VLBW preterm infants [median procedural age 23 days (range: 13–36 days), median procedural weight 1,350 g (range: 810–1,480 g), median PDA diameter 3.75 mm (range: 2.3–4.1 mm)]. The devices were Amplatzer Piccolo (n = 8). Procedures were successful in 100% and uneventful in 87.5% (7 of 8). One patient experienced mild left pulmonary artery compression intraoperatively, which resolved with device repositioning. 25% (2 of 8) patients experienced transient systemic hypertension within 24 h postoperatively, which resolved with diuretic and sedative treatment. No patients experienced ventilation or oxygenation failure, residual PDA, device malposition, or embolization. Survival to discharge was 100%. At 6-month follow-up, all patients were alive and well, without residual PDA, left pulmonary artery stenosis, and aortic coarctation.ConclusionsThe promising early and mid-term outcomes suggest that transcatheter PDA closure in VLBW preterm infants is feasible. Suitable patient characteristics, accurate PDA closure timing, and careful postoperative care are crucial determinants for procedural success. Future studies need to further expand the sample size and extend the follow-up period to evaluate the long-term efficacy and potential complications of this intervention.